2005
DOI: 10.1111/j.0030-1299.2005.13907.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological traps in isodars: effects of tallgrass prairie management on bird nest success

Abstract: 2005. Ecological traps in isodars: effects of tallgrass prairie management on bird nest success. Á/ Oikos 111: 159 Á/169.Ecological traps occur when habitat selection and habitat suitability (measured in terms of fitness) are decoupled. We developed a graphical model based on isodar theory to distinguish between an ideal distribution and an ecological trap. We tested the model's predictions using data on breeding bird populations in managed tallgrass prairie in Oklahoma. Between 1992 and 1996 we monitored succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 59 publications
5
55
1
Order By: Relevance
“…A similar pattern has been reported in studies of nesting success in many bird species (Winter & Faaborg 1999, Conway & Martin 2000, Shochat et al 2005. The pattern may be because in this part of the Middle Atlas, food resources become increasingly scarce at the end of the breeding season (MPEP 2006) so that the adults may spend more time searching for food and chicks may die from starvation.…”
Section: Discussionsupporting
confidence: 73%
“…A similar pattern has been reported in studies of nesting success in many bird species (Winter & Faaborg 1999, Conway & Martin 2000, Shochat et al 2005. The pattern may be because in this part of the Middle Atlas, food resources become increasingly scarce at the end of the breeding season (MPEP 2006) so that the adults may spend more time searching for food and chicks may die from starvation.…”
Section: Discussionsupporting
confidence: 73%
“…to complete their life cycle (Dennis et al, 1997). Moreover, the effect of the BR system on insect assemblages should also be examined at the end of the growing season, as D subplots may turn into an 'ecological trap' (Shochat et al 2005) when re-grazed after the exclusion period. Indeed, although the subplots which were not grazed during the main flowering period did attract adult insects, their eggs and larvae or nests might later have suffered from livestock disturbances in August.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that adjacent dry land area dominated by patches of shrubs and fruiting trees had also attracted a number of bird species particularly upland birds i.e., may be only facultative marsh inhabitants (Knight et al, 2001). It has been reported that birds often select habitats that offer specific foraging and nesting sites (Shochat et al, 2005;Kloskowski et al, 2010;Mcnew et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results clearly indicated that habitat selection of bird species may vary from species to species, depending upon avian behaviours such as foraging, nesting, loafing and roosting. Finally, many non habitat-related phenomena also influence the habitat selection in birds such as nest predation (Shochat et al, 2005;Marzluff et al, 2007), competition for foraging and nesting (Sherry, 2006), intraspecific attraction (Forsman et al, 2002;Rajchard, 2007;Sridhar et al, 2009) and food limitation (Musil, 2006).…”
Section: Discussionmentioning
confidence: 99%